Nanowire Growth of Bi-Te Alloy by Electrodeposition - Park, J.H.; An, B.S.; Lee, T.Y. (Asian Journal of Chemistry, 2013)
Nanowires of Bi-Te alloy were grown in the porous anodic aluminum oxide template by electrodeposition. The compositions could be obtained from about 3 to about 40 at % Bi with varying the applied voltage and the concentration of electrolytes and confirmed by energy dispersive spectroscopy. As increasing Bi3+ ion concentrations, the content of Bi in Bi-Te alloys increases. Mixture of Bi2Te3 and Te phases were confirmed by X-ray diffraction.